Intake of caffeine containing sugar diet remodels gut microbiota and perturbs Drosophila melanogaster immunity and lifespan. - Qush, A.; Al Khatib, H.A.; Rachid, H.; Al-Tamimi, H.; Al-Eshaq, A.; Al-Adwi, S.; Yassine, H.M.; Kamareddine, L. (Microbes and Infection, 2023)
The diet-microbiome-immunity axis is one among the many arms that draw up the "we are what we intake" proclamation. As such, studies on the effect of food and beverage intake on the gut environment and microbiome and on modulating immunological responses and the host's susceptibility to pathogens are on the rise. A typical accompaniment in different sustenance we consume on daily basis is the trimethylxanthine alkaloid caffeine. Being a chief component in our regular aliment, a better understanding of the effect of caffeine containing food and beverages on our gut-microbiome-immunity axis and henceforth on our health is much needed. In this study, we shed more light on the effect of oral consumption of caffeine supplemented sugar diet on the gut environment, specifically on the gut microbiota, innate immunity and host susceptibility to pathogens using the Drosophila melanogaster model organism. Our findings reveal that the oral intake of a dose-specific caffeine containing sucrose/agarose sugar diet causes a significant alteration within the fly gut milieu demarcated by microbial dysbiosis and an elevation in the production of reactive oxygen species and expression of immune-deficiency (Imd) pathway-dependent antimicrobial peptide genes. The oral intake of caffeine containing sucrose/agarose sugar diet also renders the flies more susceptible to bacterial infection and shortens their lifespan in both infection and non-infection settings. Our findings set forth additional insight into the potentiality of diet to alter the gut milieu and highlight the importance of dietary control on health.